Investigating the correlation of microstructure with stress corrosion cracking of the high-temperature heat treated 2205 duplex stainless steel - Yue Pan; Baozhuang Sun; Lixian Wang; Zhiyong Liu; Baolong Jiang; Weiting Yang; Yida Deng; Xiaogang Li (Journal of Materials Research and Technology)
Duplex stainless steels have been widely applied in many fields. However, the manufacture at high temperature may cause microstructure degradation. When served in harsh environment with external load, stress corrosion cracking (SCC) happens and threatens the safe service. In this work, the correlation of microstructure with SCC of the high-temperature heat treated 2205 duplex stainless steel was investigated. Results show that the heat treatment increases the tendency to pitting corrosion and SCC drastically attributed to the imbalanced phase ratio, coarse ferrite grains and variation in partitioning of alloy elements. The weakest zone for SCC is ferrite for the lower content of Cr and Mo and the high inter-connectivity in ferrite. SCC susceptibility can be affected by the alloy element distribution, phase proportion, ferrite grain size and austenite morphology. It is expected to provide practical and theoretical support for the processing route optimization and safe service of duplex stainless steel structures.